Dynamic mechanical analysis of poly(trimethylene terephthalate)-A comparison with poly(ethylene terephthalate) and poly(ethylene naphthalate) - Mackintosh, Allan R.; Liggat, John J. (Journal of applied polymer science, 2004)
The fiber properties of PTT have been the subject of several reports, although very few reports describe the properties of molded specimens. In this work, the dynamic mechanical relaxation behavior of compression‐molded PTT films has been investigated. The added flexibility of the PTT was found to lower the temperature of the β‐ and α‐transitions relative to the PET and PEN. The results suggest that the β‐transition is at least two relaxations for PET and PTT due to the increase in the breadth of the relaxation. The results seem to support the hypothesized mechanism of others, in that the β‐transition involves the relaxation of the carbonyl entity and the aromatic C1–C4 ring flips for PTT and PET, and the relaxation of the carbonyl for PEN. The β*‐ and α‐transitions for all three polymers seem to be cooperative in nature. © 2004 Wiley Periodicals, Inc. J Appl Polym Sci 92: 2791–2796, 2004